Pilar Membangun Ekonomi Melalui Umkm Sebagai Peluang Penyerapan Tenaga Kerja Di Indonesia - Annisa Ilmi Faried; Uswatun Hasanah; Rahmad Sembiring; Roro Rian Agustin (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2021)
In Indonesia, the pillar of economic development through MSMEs based on labor absorption plays a critical role in addressing employment issues. Where two dependent variables, specifically employment and unemployment, are present. Five independent variables are included in this analysis: investment, GDP, minimum wage, population, and the number of MSMEs. This study uses secondary data or time series for the years 2005–2019. This study's data analysis method is Simultaneous Regression. In contrast, the number of MSMEs has a positive and significant impact on employment, whereas the GDP has a negative and major impact on employment. It is necessary to determine the effect on unemployment